Amorphous material in experimentally deformed mafic rock and its temperature dependence: Implications for fault rheology during aseismic creep and seismic rupture. (September 2020) - Marti, Sina; Stünitz, Holger; Heilbronner, Renée; Plümper, Oliver
Abstract: Amorphous materials are frequently observed in natural and experimentally produced fault rocks. Their common occurrence suggests that amorphous materials are of importance to fault zone dynamics. However, little is known about the physico-chemical impact of amorphous materials on fault rheology. Here we present deformation experiments on mafic fault rock, where amorphous material forms due to intense mechanical wear during the experiments. The experiments are run at temperatures from 300 to 600 °C, confining pressures of 0.5 or 1.0 GPa, and at constant displacement rates of ( d ˙ ax ) 2 ·10 −7, 2 ·10 −8 or 2 ·10 −9 ms −1, resulting in bulk strain rates ( γ ˙ ) of ≈3 ·10 −4, 3 ·10 −5 and 3 ·10 −6 s −1 . At these conditions, the mafic rock material undergoes intense brittle deformation and cataclastic flow, but sample strength significantly decreases with increasing temperatures – a feature commonly attributed to viscous deformation processes. Microstructural analyses show that after an initial stage of homogeneous cataclastic flow, strain localizes into narrow (2–10 μm wide) ultra-cataclastic bands that evolve into amorphous shear bands. With the data presented in this research paper, we argue that the temperature sensitivity recorded in the mechanical data is caused by viscous deformation of the amorphous material. We suggest that with the formation of amorphous materials during brittle deformation, fault rheology becomes significantly temperature-sensitive. This has important implications for our understanding of fault strength and weakening due to the presence of amorphous materials. In addition, weak material along faults will lead to stress concentrations that may trigger seismic rupture. Highlights: Amorphous material causes temperature dependent fault rheology. Amorphisation occurs due to mechanical wear and not via melting. Plagioclase is a key phase as it is highly susceptible to amorphisation.